Water electrolysis and hydrogen in the European Union - Dolci, Francesco,Gryc, Katarzyna,Eynard, Umberto,Georgakaki, Aliki,Letout, Simon,Kuokkanen, Anna,Mountraki, Aikaterini,Ince, Ela,Shtjefni, Drilona,Joanny Ordonez, Geraldine,Eulaerts, Olivier,Grabowska, Marcelina (Publications Office of the European Union, 2022)
Renewable and low carbon hydrogen is both an energy carrier able to produce other fuels and downstream products, such as the e-fuels, or e-ammonia, and a decarbonised gas produced through renewable electricity. It has the potential to decarbonise hard to abate sectors which are difficult to directly electrify and play a crucial role in achieving net zero emissions target in 2050. The European Commission has recently outlined the policy context and necessary actions for the development and deployment of renewable and low carbon hydrogen within the 2030 time horizon with the Hydrogen Strategy for a Climate Neutral Europe Communication (the Hydrogen Strategy). The REPowerEU Communication4 has further addressed the joint EU and Member State actions needed in the context of the crisis triggered by the invasion of Ukraine in February 2022 and the necessity to phase out dependence on Russian supplies. The EC has strengthened the policy narrative around hydrogen and increased objectives for a pan European framework accelerating and upscaling the production of RES and low-carbon hydrogen. The main objectives and actions of the REPowerEU Plan, which build on the Hydrogen Strategy, are the deployment of several tens of GW of electrolyser capacity and the production and imports of 10 Mt and 10 Mt respectively of renewable hydrogen by 2030. Currently the most mature and promising green hydrogen production technology is water electrolysis. The main technologies considered in this report are: Alkaline electrolysis, Polymer Exchange Membrane (PEM) electrolysis, Solid Oxide electrolysis and Anion Exchange Membrane electrolysers (AEM).
10.2760/7606
Keywords: Graue Literatur; Wasserstofftechnologie; Energietechnik; Saubere Energie; EU-Staaten; hydrogen; reduction of gas emissions; energy resources; energy market; energy consumption; renewable energy; electrical energy; energy technology; value chain; research and development; competitiveness; report